Molecular mechanisms of leukocyte recruitment: organ-specific mechanisms of action - Liu, Lixin; Kubes, Paul (Thrombosis and Haemostasis, 2003)
Leukocyte recruitment in the microcirculation is a critical process underlying inflammatory responses in tissues. The mechanism of recruitment is summarized by the generally accepted paradigm: selectin-mediated leukocyte rolling, subsequent integrin activation, followed by integrin-mediated firm adhesion. This simple paradigm may not be able to explain the leukocyte recruitment mechanisms in some organs including the liver and brain. Recent studies suggested that these organs have their own leukocyte recruitment paradigms in acute and even chronic inflammation. The combination of unique hemo-dynamic patterns and specific structural and functional features of the vessels and endothelium in liver may dictate and select the specific patterns of leukocyte recruitment in this organ. In the brain microvasculature, where shears are high and adhesion molecule expression low, platelets may play an important role as a bridge between the leukocytes and endothelium.
Keywords: Inflammation; cellular interaction; selectins; integrins; liver; brain